2020
DOI: 10.1186/s12905-020-00917-7
|View full text |Cite
|
Sign up to set email alerts
|

“The best thing is that you are doing it for yourself” – perspectives on acceptability and feasibility of HPV self-sampling among cervical cancer screening clients in Tanzania: a qualitative pilot study

Abstract: Background: Cervical cancer is the most common type of cancer in sub-Saharan Africa, and it is also the cancer disease that most women die from. The high mortality rate is partly due to low attendance rates to screening services and low sensitivity of visual inspection with acetic acid, which is the standard screening method used in screening programs in sub-Saharan Africa. In order to overcome of the burden of disease new screening strategies and methods are warranted. This study aims to explore the acceptabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(73 citation statements)
references
References 38 publications
1
72
0
Order By: Relevance
“…The feasibility and acceptability of the self‐collection procedure, and the interest of the women in delivery of HPV test results via text messages were assessed by the use of five‐point Likert scales ranging from strongly agree to strongly disagree. By acceptability, we mean the women's perception/attitude towards the HPV self‐sampling procedure, 8 and by feasibility, we mean the women's abilities to conduct the HPV self‐sampling correctly and any difficulties they experienced during the self‐sampling. Good feasibility was defined as participant's ability to understand the instructions of the self‐sampling procedure and take the self‐swab in the absence of the nurse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility and acceptability of the self‐collection procedure, and the interest of the women in delivery of HPV test results via text messages were assessed by the use of five‐point Likert scales ranging from strongly agree to strongly disagree. By acceptability, we mean the women's perception/attitude towards the HPV self‐sampling procedure, 8 and by feasibility, we mean the women's abilities to conduct the HPV self‐sampling correctly and any difficulties they experienced during the self‐sampling. Good feasibility was defined as participant's ability to understand the instructions of the self‐sampling procedure and take the self‐swab in the absence of the nurse.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] Furthermore, direct and indirect economic costs, such as transportation costs, lost income, and waiting time have been found to have a negative effect on cervical cancer screening attendance. 8 In Tanzania, the standard screening method is visual inspection with acetic acid (VIA), which requires a gynecological examination. 3 A meta-analysis of 77 cross-sectional studies observed that the sensitivity of VIA to detect cervical intraepithelial neoplasia grade 2 or worse ranges between 14% and 95%.…”
Section: Introductionmentioning
confidence: 99%
“…In future, by coupling care HPV testing with HPV self‐collection, the screening service could be brought even closer to women, especially to older women living in remote areas. Such an approach is supported by the findings from a qualitative study conducted in Tanzania in which the majority of the women preferred self‐sampling over provider‐based sampling 29 …”
Section: Discussionmentioning
confidence: 93%
“…Such an approach is supported by the findings from a qualitative study conducted in Tanzania in which the majority of the women preferred self-sampling over provider-based sampling. 29 When considering implementing HPV testing to identify women at highest risk of HSIL + , it is of great importance that the screening is coupled with systematic treatment. This can be implemented by a see-and-treat approach where HPV-positive women undergo colposcopy, digital cervicography or VIA and -if positive -subsequent treatment.…”
Section: Ta B L Ementioning
confidence: 99%
“…The uptake and scale-up of such emerging screening approaches largely depend on knowledgeable, motivated and capable health-care providers that are well respected by the communities they serve. A recent study from Tanzania showed that even though self-sampling was perceived as acceptable there was a high demand for nurse presence during self-sampling [ 22 ], which points to the importance of health-care providers for and during the self-sampling screening process.…”
Section: Introductionmentioning
confidence: 99%